Eat, Cook, Grow: Mixing Human-Computer Interactions with Human-Food Interactions - Choi (MIT Press, 2014)
Monograph
fulltext
Keywords: General Topics for Engineers; Communication, Networking and Broadcast Technologies; Computing and Processing